The effect of parenting styles on Chinese undergraduate nursing students’ academic procrastination: the mediating role of causal attribution and self-efficacy - Li, Yuanyuan; Dong, Wanglin; Tang, Haishan; Guo, Xiajun; Wu, Sijia; Lu, Guangli; Chen, Chaoran (Frontiers in Psychology, 2023)
Background Academic procrastination is common among college students, but there is a lack of research on the influencing mechanism of academic procrastination among nursing students. The purpose of this study was to explore the influence of parental rearing patterns on academic procrastination of nursing students, and the mediating role of causal attribution and self-efficacy. Methods Using Parental Bonding Instrument, Aitken Procrastination Inventory, Multidimensional Multi-Attribution Causality Scale and General Self-Efficiency Scale, the data of 683 nursing undergraduates from two universities in China were collected. Moreover, path analysis for structural equation modeling via AMOS 26.0 to evaluate mediation path model. Results Positive parenting style was negatively associated with academic procrastination (r = –0.350) and negative parenting style was positively associated with academic procrastination (r = 0.402). Positive parenting style directly or indirectly predicted academic procrastination through the mediating effect of internal attributional style (β = –0.10, 95% CI: –0.18 to –0.04) and self-efficacy (β = –0.07, 95% CI: –0.11 to –0.03), and this mediating effect accounted for 41.46% of the total effect. Positive parenting style directly or indirectly predicted academic delay through the mediating effect of external attributional style (β = 0.12, 95% CI: 0.07 to 0.17) and self-efficacy (β = 0.05, 95% CI: 0.03 to 0.08), and this mediating effect accounted for 42.5% of the total effect. In addition, causal attribution and self-efficacy of nursing students play a chain intermediary role between parenting style and academic procrastination. Conclusion Parents should give students more care and autonomy and reduce control. In addition, educators should give students attribution training, which is helpful to improve students’ self-efficacy and reduce academic procrastination.